2021
DOI: 10.3846/tede.2021.15781
|View full text |Cite
|
Sign up to set email alerts
|

Do Economic Growth and Environment Quality Contribute to Tourism Development in Eu Countries? A Panel Data Analysis

Abstract: The positive impact of the tourism industry on economic growth, revenues, infrastructure, employment, social inclusion and poverty reduction, although widely recognised, has been lately weighted against the appearance and exacerbation of several problems, such as: environmental footprint, increase of income inequality, cost increases related to solid waste collection, energy consumption, increased global CO2 emissions. On the other hand, the tourism sector is not just an active economic, societal, or environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 112 publications
0
10
0
Order By: Relevance
“…We chose EU27 data because most European Union countries have a long tradition of environmental and healthcare policies, the tourism sector is likewise well-developed and representative and statistical data are easily accessible, harmonized across member states and available for the entire analyzed period. In particular, the present paper builds on our previous research on the relationship between environmental quality and tourism development, and between economic growth, pollution and health in EU countries [64][65][66].…”
Section: Methodsmentioning
confidence: 99%
“…We chose EU27 data because most European Union countries have a long tradition of environmental and healthcare policies, the tourism sector is likewise well-developed and representative and statistical data are easily accessible, harmonized across member states and available for the entire analyzed period. In particular, the present paper builds on our previous research on the relationship between environmental quality and tourism development, and between economic growth, pollution and health in EU countries [64][65][66].…”
Section: Methodsmentioning
confidence: 99%
“…A good number of studies already examines the relationship between tourism and CO 2 , mostly using panel data analysis namely, EU Countries (Ahmad et al, 2019;Arbulú et al, 2015;Badulescu et al, 2021;Dritsaki and Dritsaki, 2014;Paramati et al, 2017), Asia (Ahmad et al, 2019), ASEAN 5 (Azam et al, 2020;Tang and Tan, 2015), Gulf Cooperation Council (Alhowaish, 2016), Mediterranean countries (Dritsaki and Dritsaki, 2014), Muslim Countries (Muhammad et al, 2021), and OECD (Liddle, 2012). While the other research studies focuses on countries level of data for example Italy (Ercolano et al, 2018), Pakistan (Khan et al, 2020;Khan and Ahmad, 2021;Liu et al, 2019), China (Tang et al, 2014;Udemba, 2019), Turkey (Koçak et al, 2020), Cyprus (Katircioglu et al, 2014), Spain (Mateu-Sbert et al, 2013, Switzerland (Jaligot and Chenal, 2018).…”
Section: The Relationship Between Tourism and Comentioning
confidence: 99%
“…Recent studies on the EU sample (Gardiner & Hajek, 2020;Dogan & Aslan, 2017) demonstrated that CO 2 emissions affect GDP in both the old and new EU countries with the negative relationship confirmed in the old EU countries. Interestingly, Badulescu et al (2021) examined the nexus between tourism, GDP growth and CO 2 emissions in 27 EU member states for the 1995-2016 period. They noted the negative impact of GDP growth and CO 2 emissions on tourism development.…”
Section: Literature Reviewmentioning
confidence: 99%